(untitled) (Jurnal Bahasa, 2016)
This paper aims in suggesting rules on consonant changes in Indonesian rhyming reduplication. This paper argues that consonant changes in Indonesian rhyming reduplication can be elucidated through an independent approach which does not treat two other types of rhyming reduplication, i.e. vowel-changing and syllable-changing. The four rules on consonant-changing rhyming reduplication are proposed based on the following characteristics: (1) only native phonemes can be changed, (2) consonant changes shift to bilabial sounds in normal situations, (3) consonants are usually changed only in the first syllable, and (4) the presence or absence of [voice] feature corresponds to a basic unit in consonant changes and, in principle, the meaning "diverse", "superlative" or "very" can be derived from a change of [sonorant] feature. This study also investigates whether the consonant change patterns in the rhyming reduplicated form can be analyzed according to these four rules. This study also examines the relations between three types of Indonesian rhyming reduplications in describing the remaining problems. Keywords: Indonesian, consonant change, rhyming reduplication, rhyming reduplicated word, independent approach